What's new in genitourinary pathology 2023: WHO 5th edition updates for urinary tract, prostate, testis, and penis - Bonnie Choy; Maria Tretiakova; Debra L. Zynger (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
The 5th edition WHO Classification of Urinary and Male Genital Tumours (2022) introduced many significant changes relevant to urologic daily practice, mainly to renal tumors which was covered in the What's New newsletter in September 2022. In this newsletter, we summarize the notable changes to bladder, prostate, testis, and penis based on the 5th edition of the WHO.